Atrophic mandibular fracture treatment: prototyping as a tool in surgical planning (Research, Society and Development, 2020)
Introduction: Atrophic mandibular fractures are injuries found in old age due to facial trauma. Its treatment is a challenge, even for experienced surgeons, due to the different approaches that can be taken from clinical decisions. Taking into consideration the limitations that the age presented by most of the affected patients brigs, there are devices that stand out by seeking benefits in terms of predictability and time gain in the intraoperative period. The additive manufacturing is a valuable resource in the surgical planning and rehabilitation of these patients. Objective: To expose a clinical case that demonstrates the success in the use of surgical planning through a prototype printed in 3D technology. Clinical case: Elderly woman, 75 years old, victim of a fall from her own height who had a bilateral atrophic mandible fracture due to facial trauma. The surgical procedure was planned using a prototype printed in 3D technology providing predictability and reduced surgical time. The patient evolved in the postoperative period without complaints, with function immediately restores and without signs of infection or plate exposure. Conclusions: Atrophic mandible fractures are still related to a challenging treatment, therefore, adequate surgical planning and the use of auxiliary strategies such as 3D prototyping provide greater predictability of results, as well as time gain during the intraoperative.